Tuk Sikopyah Water Taking Ritual to Revitalize Local Wisdom in Anticipating Drought in Serang Village - Tuti Supriyanti Asofi; Eva Banowati; Rahma Hayati (JESS (Journal of Educational Social Studies), 2023)
This paper aims to describe the local wisdom values of the Tuk Sikopyah Ritual in Serang Village, explain their inheritance, and analyse the water management in overcoming drought. The research employed a mixed method. The qualitative method was used to examine the data dealing with explaining the local wisdom values of the Tuk Sikopyah Ritual and the ways of their inheritance to the younger generation; whilst the quantitative method was to calculate the usage of the water in meeting daily water needs of Serang community. It was found that seven kinds of noble values are practised in the Tuk Sikopyah water-taking ritual. The seven noble values are concerned with the existence, utilization, and preservation of the Tuk Sikopyah water spring. The caretaker collaborates with the clerics and local government to teach and inherit the local wisdom values in the Tuk Sikopyah water-taking ritual.  The calculation showed that only around 72.80% of the Tuk Sikopyah water debit (calculation in the dry season) were used to fulfil the daily need of the community of Serang Village.